The safety and efficiency of scissor-type knives in colorectal Endoscopic submucosal dissection: An International multicenter observational study - Liu, Kuilang; Wu, Jing; Tamaru, Yuzuru; Wang, Yadan; Su, Hui; Guo, Chunmei; Wang, Canghai; Liu, Hong; Kobayashi, Makoto; Honma, Kiyoaki; Yamada, Takuya; Evgeniy, Levchenko; Mohammed, Noor; Cadoni, Sergio; Parra-Blanco, Adolfo; Mariya, Antipova; Ishaq, Sauid; Kuwai, Toshio (Endoscopy International Open)
Background and Aims: Scissor-type knives have shown safety and efficacy in endoscopic submucosal dissection (ESD) procedures, particularly in studies from Japan. However, the safety and efficacy of these devices in international settings, particularly outside Japan is not well established. Methods: This is prospective, multicenter, observational study conducted across nine international centers, encompassing a total of 461 lesions from 460 patients. In subgroup analysis, 162 lesions came from four institutions in Japan (Japanese institutions group, JAG) and 299 lesions from five institutions outside Japan ( non-Japanese institutions group, NJAG).After 1:1 propensity score matching resulted in 120 matched pairs of lesions， key outcomes were compared between groups. Results: The overall perforation rate during ESD procedures was 0.87%. Intraoperative perforations were observed more frequently in NJAG than JAG (3 vs 1 event, 1.9% vs. 0.33%, respectively), although not statistically significant (p = 0.127). The overall incidence of delayed bleeding was also 0.87%, with no delayed bleeding reported in NJAG. Post propensity matching analysis revealed a significantly slower median resection speed in NJAG compared to JAG(9.12 0.86–56.57 vs 26.21 1.95–93.54 mm²/min, p < 0.001). Both histological complete resection and curative resection rates were significantly lower in NJAG than in JAG with rates of 88.3% vs 98.3% for histological complete resection and 83.3% vs 95% for curative resection (both p < 0.01). Conclusions: The use of scissor-type knives in colorectal ESD outside Japan demonstrated a favorable safety profile. However, certain performance outcomes, such as resection speed and resection success rates, were inferior to Japanese institutions.